2018
DOI: 10.1111/cogs.12620
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Learning May Contribute to Phonetic Learning in Infants: A Corpus Analysis of Maternal Spanish

Abstract: In their first year, infants begin to learn the speech sounds of their language. This process is typically modeled as an unsupervised clustering problem in which phonetically similar speech-sound tokens are grouped into phonetic categories by infants using their domain-general inference abilities. We argue here that maternal speech is too phonetically variable for this account to be plausible, and we provide phonetic evidence from Spanish showing that infant-directed Spanish vowels are more readily clustered o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…cal studies indicated that children selectively, and more readily, learn words that contain phonemes they are able to produce (Ferguson & Farwell, 1975;Leonard et al, 1981;Schwartz & Leonard, 1982;Stoel-Gammon & Cooper, 1984). In contrast, recent work employing computational models highlight the role of higher-level lexical knowledge in guiding children's acquisition of phonetic categories by providing informative cues about sounds that occur together in words (Feldman et al, 2013;Swingley, 2019;Swingley & Alarcon, 2018). Preschool children's perception of the phonological make-up of words, which is supported by the phonemic diversity of their own speech, is a strong predictor of long-range literacy outcomes, including reading skill (Wagner et al, 1997).…”
Section: Research Highlightsmentioning
confidence: 99%
“…cal studies indicated that children selectively, and more readily, learn words that contain phonemes they are able to produce (Ferguson & Farwell, 1975;Leonard et al, 1981;Schwartz & Leonard, 1982;Stoel-Gammon & Cooper, 1984). In contrast, recent work employing computational models highlight the role of higher-level lexical knowledge in guiding children's acquisition of phonetic categories by providing informative cues about sounds that occur together in words (Feldman et al, 2013;Swingley, 2019;Swingley & Alarcon, 2018). Preschool children's perception of the phonological make-up of words, which is supported by the phonemic diversity of their own speech, is a strong predictor of long-range literacy outcomes, including reading skill (Wagner et al, 1997).…”
Section: Research Highlightsmentioning
confidence: 99%
“…While infants are learning the sounds of their language, they have access to other rich acoustic and contextual information in the input, and they can rely on their emerging lexical knowledge in this process (Swingley, 2009). In their first year of life, infants learn the sounds but also words of their native language (Bergelson & Swingley, 2012), and early knowledge of word forms can guide them in finding lexically relevant speech contrasts in their language, especially for cases when the distributional properties of specific sound categories are not easily differentiated in the input (Swingley & Alarcon, 2018).…”
mentioning
confidence: 99%
“…Other results in the literature accord well with the notion that type-level statistics are relevant in phonetic learning. Such effects have been shown in several experimental studies of infants and toddlers Thiessen, 2007;Thiessen & Yee, 2010;Yeung & Werker, 2009) and supported in corpus modeling work on the acquisition of vowel categories (Swingley & Alarcon, 2018). In adults, some phonological generalizations appear to track type frequency rather than token frequency (Hay, Pierrehumbert, & Beckman, 2004), and in children, phonological representations have been argued to gain fidelity through participation in multiple different words (Edwards, Beckman, & Munson, 2004).…”
Section: Discussionmentioning
confidence: 75%